The effect of proprioceptive training on technical soccer skills in female soccer - Souglis, A. G.; Travlos, A. K.; Andronikos, G. (International Journal of Sports Science & Coaching, 2023)
Development of perceptual-cognitive motor skills is a crucial factor influencing soccer training and competition. The aim of the study was to examine the effects of neuromuscular coordination, proprioceptive and balance exercises on physiological attributes and technical skills in female soccer. Female soccer players competing in Greek A Division (N = 48) were assigned to intervention (N1 = 24) and control groups (N2 = 24). The Proprioceptive Training Intervention Program (PTIP) lasted approximately 20 min and was implemented five times per week for 16 weeks. It was hypothesized that the PTIP in addition to a regular training programme would significantly affect female soccer player perceptual-cognitive-motor capability as it was estimated with physiological attributes (VO2max and agility) and motor performance soccer technical skills (juggling, heading, shooting, passing, and dribbling). All performance variables were measured prior and after the 16-weeks PTIP. Groups by Measures (2 × 2) ANOVAs with repeated measures on the second factor revealed that the intervention group decreased percent body fat and improved VO2max and all technical skills in comparison to the control group after the PTIP (p < 0.05). The findings demonstrate the beneficial role of a proprioceptive training programme on both physiological attributes and technical skills in female soccer. Practical implications include the application of the intervention programme for monitoring and developing soccer players while also the use of the assessment tests to evaluate players.